Development of baby food from cavendish banana - Sagun, Filomena Yadao
This study aimed to develop an acceptable baby food from Cavendish. The study developed a formulation and a process to produce an acceptable and safe baby food from Cavendish banana. The standard banana puree formulation was modified by varying the banana to water ratio, and the formulation chosen was adopted as the baby food formulation since banana puree are primarily produced for baby food. The most acceptable banana to water ratio was determined. According to sensory evaluations results, 1:0.5 ratio and 33% water level was the most acceptable. The process schedule was determined using the formulation chosen form phase I. Three schedules were tested- 10, 15, and 20 minutes processing at 212°F in water bath. Heat penetration study determined 20 minutes processing to be an adequate process. Mesophilic spore-forming (Byutic anaerobes and B. mecerans) were the reference organisms and the order of the process is 5 (Alabastro, 1987). Based on this, Fo was computed to be 2.5 minutes at D equal to 0.5 and z value at 16. Fc of 20 minutes processing is 4.5 minutes which much greater than Fo. Ten and fifteen minutes processing had Fc value of 0.64 and 0.92 minute, respectively. Compared to Fo value, these process schedules were inadequate. The chosen process schedule was standardized. Pilot scale production was conducted to produce the final product. The process applied was evaluated to be adequate. Quality assessment and sensory evaluations of the baby food from Cavendish were conducted after equilibrating the product. Physico-chemical test include pH, %SS, TA, viscosity and color. The pH of the baby food slightly changed from 4.0 to 4.1 after two weeks of storage at room temperature. Storage at refrigeration temperature did not affect the pH of the product. After two weeks of storage, %SS increased to 14.6 to 14.4 at room and refrigeration temperature storage, respectively. Consistency/viscosity slightly changed from 564996 to 55136 centipoise after two weeks of storage at room temperature. The color of the raw material changed from 2.5 Y 8/8 to 10YR 8/6. Proximate composition of the baby food determined were crude protein - 1.0 g and carbohydrate was computed to be approximately 15.6 g. Vitamin C content of the product was determined to be 77 mg. Calcium, potassium and sodium were detected to 13.3, 38.8 and 127.9 mg respectively. The cost analysis of the baby food from Cavendish banana showed that it is cheaper than the commercially available banana food by 33% (based on per gram price). A 71 gram bottled banana Gerber costs P24.50 while a 170 gram bottled experimental product costs P19.60.